The impact of IVF on deep invasive endometriosis. (October 2019) - Berlanda, Nicola; Benaglia, Laura; Bottelli, Lara; Torri, Chiara; Busnelli, Andrea; Somigliana, Edgardo; Vercellini, Paolo
Abstract: Objective: Ovarian hyper-stimulation during IVF is associated with a significant raise in serum estrogens and one may expect detrimental effects on estrogen-dependent diseases such as endometriosis. However, available evidence from large case series of affected women performing IVF is generally reassuring with the possible exception of women carrying deep invasive lesions. On this basis we deemed important investigating more in depth whether women with deep invasive endometriosis could be a subgroup at higher risk of recurrence or disease progression during IVF. Study design: Women with endometriosis who underwent IVF and who had a second evaluation after 3–6 months from a failed cycle were retrospectively reviewed. The main inclusion criteria were the presence of deep invasive endometriosis and/or a history of surgery for this form of the disease. The primary aim of the study was to determine the frequency of endometriosis-related complications in the interval between the two evaluations. Secondary aims were pain symptoms and lesion size modifications. Results: Eighty-four women were ultimately selected: baseline ultrasound documented deep invasive lesions in 60 of them. One case of possible endometriosis-related complication was recorded, corresponding to a rate of 1.2% (95%: 0.05%–5.5%) for the whole cohort and 1.7% (95%CI: 0.08–7.6%) for the subgroup of women with ultrasound detected lesions. This rate appears similar to the reported frequency of endometriosis progression in women not receiving IVF. No significant modifications in pain symptoms or lesions size occurred. Conclusions: Women with deep invasive endometriosis who underwent IVF do not seem to be exposed to a substantially increased risk of recurrence/disease progression. Larger evidence from independent groups is however required for a definitive conclusion.